Intradural herniation of a thoracic disc presenting as left radicular pain and left drop foot - Takuji Matsumoto; Muneharu Ando; Hiromi Hamazaki (Interdisciplinary Neurosurgery, 2015)
Intradural disc herniation is a rare pathological entity. Normally, it is associated with severe neurological deficits, including compression syndrome of the spinal cord or cauda equina. Intradural disc herniations comprise 0.26% to 030% of all herniated discs. Overall, 5% are found in the thoracic region, 3% in the cervical region, and 92% in the lumbar region. Although intradural disc herniation may be suspected preoperatively because of myelography, computed tomography, and magnetic resonance imaging results, establishing the diagnosis before surgery is difficult. We report a patient with thoracic intradural disc herniation at T11-12 who presented with left radicular pain and left drop foot. Preoperative magnetic resonance imaging, computed tomography, and myelography failed to demonstrate an intradural lesion. The patient underwent T11-L1 dorsal hemilaminectomy with lateral extension to the left side. The herniation was identified only intraoperatively during inspection of the thecal sac. The disc was removed surgically, and the operation was performed safely under intraoperative spinal cord monitoring. The patient had a good neurological recovery. She remains pain-free 2 years after the surgery.